2021
DOI: 10.1111/1750-3841.15663
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glass transition and hydration on the biological stability of dry yeast

Abstract: The purpose of this study was to determine the effects of glass transition and hydration on the storage stability of baker's dry yeast (Saccharomyces cerevisiae). The glass transition temperature (T g ) of the yeast decreased with increase in water activity (a w ), and a w at which glass transition occurs at 25 • C was determined as the critical a w (a wc ). From mechanical relaxation measurements at 25 • C, the yeast exhibited a large mechanical relaxation above the a wc , and the degree of mechanical relaxat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Due to the high T g (162 °C) reported for DE of 17–21, 49 it was possible to reduce the stickiness problem encountered when YCs were applied as the carrier material. Because of the low T g values of baker's dry yeast, between 53.7 and 35.7 °C when yeast samples had an a w value between 0.112 and 0.323, and moisture content of 5.6–7.14%, 50 the yeast cells by themselves could not be enough to increase T g of OMW. In the studies, encapsulating bioactive compounds such as ethanolic extracts of grape pomace, 23 pumpkin peel, 27 and flavor oils 24 into yeast cells, the spray-drying yield was not given, therefore we could not make a comparison with our study.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high T g (162 °C) reported for DE of 17–21, 49 it was possible to reduce the stickiness problem encountered when YCs were applied as the carrier material. Because of the low T g values of baker's dry yeast, between 53.7 and 35.7 °C when yeast samples had an a w value between 0.112 and 0.323, and moisture content of 5.6–7.14%, 50 the yeast cells by themselves could not be enough to increase T g of OMW. In the studies, encapsulating bioactive compounds such as ethanolic extracts of grape pomace, 23 pumpkin peel, 27 and flavor oils 24 into yeast cells, the spray-drying yield was not given, therefore we could not make a comparison with our study.…”
Section: Resultsmentioning
confidence: 99%
“…As a typical parameter, ∆ F (the force difference between initial compression and compression after 3 min) was evaluated from the isothermal mechanical relaxation curves as described in previous studies. 5) 27) 28) …”
Section: Resultsmentioning
confidence: 99%
“…The T g of the a w -adjusted C. sakazakii cells was determined by thermal rheological analysis (TRA) as described in previous studies ( 37 40 ) and as shown in Fig. 5 .…”
Section: Methodsmentioning
confidence: 99%